Epigenetic regulation of gene expression in human malaria parasite Plasmodium falciparum. - Tan, Corinna Cailing. (2011)
Plasmodium falciparum is the most lethal species of the Plasmodium genus. Epigenetic regulation is one of the key regulations that enable parasites to perform rapid transitions throughout their lifecycle and antigenic variations to sustain chronic infections. Using ChIP-on-chip, we studied Post-translational modification (Acetylation) on core histone H4- lysine 8 (H4K8ac) and lysine 16 (H4K16ac) on P. falciparum strain Dd2 and Tetra-acetylation (H4ac4) for another P. falciparum strain 3D7. We also observed the enrichment of these modifications on certain genes across the intraerythrocytic developmental cycle (IDC) of the parasite. A bimodal distribution in the correlations between enrichment and their corresponding expression profiles of all modifications, showing the modulation of gene expression. It was suggested that epigenetic regulation could take place more within intragenic regions than intergenic regions. Interestingly, the comparison between the two different P. falciparum strains of H4K8ac and H4K16ac modification showed similarity in gene enrichment and functional enrichment analysis gave greater insights into the physiological relevance of these epigenetic modifications.